(untitled) (Journal of the College of Basic Education, 2022)
The family is considered the first social body that is responsible for preparing the individual for the future of his life, and for carrying out his role in society, and which transmits to him the opinions, beliefs, values, and customs prevailing in that society, as his biological and psychological needs are satisfied through the mother in the first place, then the father, followed by The rest of the family members help him to satisfy these needs sufficiently through love and tenderness (Abdullah, 1980: 38). Which actually affects the demolition of the natural foundations of the family, we find it among the most dangerous destructive factors for the child’s personality socially, psychologically, culturally and morally